PENGARUH TERPAAN PARIWISATA DAN MEDIA MASSA TERHADAP PRESTASI BELAJAR PESERTA DIDIK MTSN PANGANDARAN KABUPATEN CIAMIS - Patimah, Patimah (IAIN Ponorogo, 2013)
Abstract: The tourism resort as a social environment and mass media as a non- social environment will affect student learning outcomes. Studies on those effects on learning achievement seem to be essential to do. By employing descriptive and explanatory methods, this study attempted to investigate the influence of tourism and mass media exposure on student achievement. The results showed that firstly, the average exposure to tourism was at a high level with the score of 144 laid on the high range of 138-160; secondly, mass media exposure was in the rate of high level with the score of 141Â between the range of 138-160 (high); thirdly, student achievement on average was at a moderate level with the score of 75 laid between the range of 56-75 (moderate); the fourth, there was any significant effect of tourism exposure on student achievement at the high level with the value of r = 0.66 ranging between .61 to .80 (high); the fifth, there was any significant effect of mass media exposure on student achievement at the high level with the value of r = 0.71 ranging between .61 to 0 , 80 (high); the sixth, a significant difference between mass media and tourism exposures on student achievement was at the high level of closeness with the score value of r = 0.75 laid between 0.61 to 0.80 (high).Â Ø§Ù ÙÙØ±Ø«Ø£Øª Ø§Ù ÙÙÂ -Ø©ÙØ¹Ø§Ù ØªØ¬ÙØ§Ø§ ÙØ±Øº Ø©Ø¦ÙØ¨ÙØ§Ù - Ù ÙØ§Ø¹ÙØ§Ø§ ÙØ¦Ø§Ø³ÙÙ - Ø©ÙØ¹Ø§Ù ØªØ¬ÙØ§Ø§ Ø©Ø¦ÙØ¨ÙØ§Ù - Ø©ÙØØ§ÙØ³ÙØ§ Ø©Ø¦ÙØ¨ÙØ§ :ØµØ®ÙÙ Â Ø§Ø°Ù ÙØ´ØªÙØ§ .Ø§Ø¨Ø§Ù Ø°Ø¬ Ø§Ø¹ÙØ¶ÙÙ Ø¨ÙØ§Ø·ÙØ§ Ù ÙØ¹Øª Ø©Ø¬ÙØªÙ ÙÙØ¹ Ø§Ù ÙÙØ±Ø«Ø£Øª ÙÙ Ø©Ø³Ø§Ø±Ø¯ÙØ§ ÙÙÙØªÙ .Ø¨ÙØ§Ø·ÙØ§ Ù ÙØ¹Øª Ø©Ø¬ÙØªÙ ÙÙØ¹Â Ø©Ø¬ÙØªÙ ÙÙØ¹ )Ø§Ø¹Ù (Â Ù ÙØ§Ø¹ÙØ¥Ø§ ÙØ¦Ø§Ø³ÙÙ ÙØØ§ÙØ³ÙØ§ Ø±ÙÙØ¸ÙØ§ ÙØ±Ø«Ø£Øª ÙØ¯Ù ÙÙØ§ÙØ¨ÙØ§Ù ÙÙÙÙÙØ§ Ø«ØØ¨ÙØ§ Ø¨ÙÙØ³Ø£Ø¨ â Ø«ØØ¨ÙØ§Â Ø©Ø¬ÙØªÙÙØ§Ø¨ Ø©ÙÙØ§Ø¹ÙØ§ Ø©Ø¬Ø±Ø¯ÙØ§ ÙÙ Ø©ÙØ¯Ø§Ø¹ÙÙ Ø§Ø¨ Ø©ÙØØ§ÙØ³ÙØ§ Ø©Ø¨Ø§ØµÙØ¥Ø§ ØªÙØ§Ù )1 : Ø©ÙÙØ§ØªÙØ§ Ø¬Ø¦Ø§ØªÙÙØ§Ø¨ Ø©Ø³Ø§Ø±Ø¯ÙØ§ ØªØªØ£Ù .Ø¨ÙØ§Ø·ÙØ§ Ù ÙØ¹ØªÂ 141Ø©Ù ÙÙÙØ§Ø¨ Ø©ÙÙØ§Ø¹ÙØ§ Ø©Ø¬Ø±Ø¯ÙØ§ ÙÙ Ø©ÙØ¯Ø§Ø¹ÙÙ Ø§Ø¨ Ù ÙØ§Ø¹ÙØ¥Ø§ ÙØ¦Ø§Ø³Ù Ø©Ø¨Ø§ØµØ¥ ØªÙØ§Ù )2 .)Ø©ÙÙØ§Ø¹( 160-138 ÙÙØ¨ ÙÙÙØª 144Â ÙÙØ¨ ÙÙÙØª 75 Ø©Ù ÙÙÙØ§Ø¨ Ø©Ø·Ø³ÙØªÙÙ Ø§ Ø©Ø¬Ø±Ø¯ÙØ§ ÙÙ ÙÙÙÙ Ø©ÙØ¯Ø§Ø¹ÙÙ Ø§Ø¨ Ø¨ÙØ§Ø·ÙØ§ Ø²Ø§ÙØ¬Ø¥ )3. )Ø©ÙÙØ§Ø¹( 160-138 ÙÙØ¨ ÙÙÙØªÂ Ø©Ø¬Ø±Ø¯ÙØ§ ÙÙ Ø¨ÙØ§Ø·ÙØ§ Ù ÙØ¹Øª Ø²Ø§ÙØ¬Ø¥ ÙÙØ¹ Ø©ÙØØ§ÙØ³ÙØ§ Ø©Ø¨Ø§ØµÙØ¥Ø§ ÙÙ ÙÙØ¹Ù ÙØ° ÙØ±Ø«Ø£ØªÙØ§ Ø¯Ø¬ÙÙ )4 .)Ø©Ø·Ø³ÙØªÙ ( 75-56Â ÙØ¦Ø§Ø³Ù Ø©Ø¨Ø§ØµØ¥ ÙÙ ÙÙØ¹Ù ÙØ° ÙØ±Ø«Ø£ØªÙØ§ Ø¯Ø¬ÙÙ )5 Ø)Ø©ÙÙØ§Ø¹(Â 0,80-0,61 ÙÙØ¨ ÙÙÙØªÂ 0,66 = r Ø©Ù ÙÙÙØ§Ø¨ Ø©ÙÙØ§Ø¹ÙØ§Â Ø )Ø©ÙÙØ§Ø¹(Â 0,80-0,61 ÙÙØ¨ ÙÙÙØª 0,71 =r Ø©Ù ÙÙÙØ§Ø¨ Ø©ÙÙØ§Ø¹ÙØ§ Ø©Ø¬Ø±Ø¯ÙØ§ ÙÙ Ø¨ÙØ§Ø·ÙØ§ Ù ÙØ¹Øª Ø²Ø§ÙØ¬Ø¥ ÙÙØ¹ Ù ÙØ§Ø¹ÙØ¥Ø§Â Ø©Ø¬Ø±Ø¯ÙØ§ ÙÙ Ø¨ÙØ§Ø·ÙØ§ Ù ÙØ¹Øª Ø²Ø§ÙØ¬Ø¥ ÙÙØ¹ )Ø§Ø¹Ù ( Ù ÙØ§Ø¹ÙØ¥Ø§ ÙØ¦Ø§Ø³Ù Ù Ø©ÙØØ§ÙØ³ÙØ§ Ø©Ø¨Ø§ØµÙØ¥Ø§ ÙÙØ¨ ÙÙØ¹Ù ÙØ° ÙØ±Ø«Ø£ØªÙØ§ Ø¯Ø¬ÙÙ )6.)Ø©ÙÙØ§Ø¹( 0,80 â 0,61 ÙÙØ¨ ÙÙÙØªÂ 075=r Ø©Ù ÙÙÙØ§Ø¨ Ø©ÙÙØ§Ø¹ÙØ§